Preparation and use of DMF-stabilized iridium nanoclusters as methylation catalysts using methanol as the C1 source - Oikawa, Kei; Itoh, Satoshi; Yano, Hiroki; Kawasaki, Hideya; Obora, Yasushi (Chemical communications (Cambridge, England), 2017)
We report methylations of alcohols and anilines catalyzed by DMF-stabilized Ir nanoclusters using methanol as the C1 source. The DMF-stabilized Ir nanoclusters were prepared in one step and have diameters of 1–1.5 nm. They react in a borrowing-hydrogen reaction and are efficient methylation catalysts (TON up to 310 000).